Respuesta :

Bxrii

Answer:

No, not necessarily

Step-by-step explanation:

When you subtract 3x to the other side you dont want to forget abt that other number, since 1 is a positive it is going to be a + 1

the correct answer is C

y = -3x + 1

High Hopes <3

Bxrii

━━━━━━━☆☆━━━━━━━

▹ Answer

y = 1 - 3x

▹ Step-by-Step Explanation

3x + y = 1

Move the variable to the right side, and change the sign:

y = 1 - 3x

Hope this helps!

- CloutAnswers ❁

Brainliest is greatly appreciated!

━━━━━━━☆☆━━━━━━━

ACCESS MORE